2018
DOI: 10.1002/bkcs.11380
|View full text |Cite
|
Sign up to set email alerts
|

Direct Nitradated Graphite Felt as an Electrode Material for the Vanadium Redox Flow Battery

Abstract: The vanadium redox flow battery (VRFB) is one of the most promising electrochemical energy storage systems for grid support. However, the electrochemical performance of the VRFB should be further improved for successful penetration into the large‐scale energy storage system market. Among all the components of the VRFB, the electrode, which provides an active site for the vanadium ion redox reaction, plays an important role in determining the electrochemical properties of the VRFB. In this work, nitrogen‐doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Kim et al heat-treated graphite felt in a stream of NH 3 to achieve direct nitridation [358]. Wettability was not affected, but improved energy efficiency after an optimum treatment temperature of 850 • C was found for the initial 50 cycles.…”
Section: Mechanical Thermal or Chemical Surface Treatmentmentioning
confidence: 99%
“…Kim et al heat-treated graphite felt in a stream of NH 3 to achieve direct nitridation [358]. Wettability was not affected, but improved energy efficiency after an optimum treatment temperature of 850 • C was found for the initial 50 cycles.…”
Section: Mechanical Thermal or Chemical Surface Treatmentmentioning
confidence: 99%
“…Inspired by these notions, Shao et al [ 76 ] applied nitrogen doping for VRFB electrode modification to promote the electrochemical properties of the VO 2+ /VO 2 + redox couple for VRFBs. Since then, besides nitrogen [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], doping with other heteroatoms, such as phosphorus [ 87 ], halogen, and boron [ 88 , 89 , 90 , 91 ], as well as dual doping with carbon–nitrogen [ 92 , 93 , 94 , 95 ], phosphorus-doped C 3 N 4 [ 96 ], oxygen–nitrogen [ 97 , 98 , 99 , 100 , 101 ], oxygen–phosphorus [ 102 , 103 ], fluorine–phosphorus [ 104 ], nitrogen–phosphorus [ 105 ], and nitrogen–sulfur [ 106 ], have been applied in VRFBs and demonstrated excellent rate performance and outstanding cycling stability.…”
Section: Literature Review Of Modification Of Carbonous Feltmentioning
confidence: 99%
“…[18,19] J. Jin et al found that introducing nitrogen-containing functional group (nitrogen-doped) was an effective method to improve the electrochemical activity of carbon-based materials. [20][21][22] Their research also stated that among four types of nitrogen-doped species including pyridinic-N, pyrrolic-N, graphitic N, and oxidic-N, graphitic N was a catalytic active center for the VO 2 + /VO 2 + couple. In this work, we propose a simple ammonium sulfate hydrothermal method to prepare the nitrogen-doped carbon felts to improve electrochemical activity and hydrophilicity (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…J. Jin et al. found that introducing nitrogen‐containing functional group (nitrogen‐doped) was an effective method to improve the electrochemical activity of carbon‐based materials [20–22] . Their research also stated that among four types of nitrogen‐doped species including pyridinic‐N, pyrrolic‐N, graphitic N, and oxidic‐N, graphitic N was a catalytic active center for the VO 2+ /VO 2 + couple.…”
Section: Introductionmentioning
confidence: 99%